State and trends in the development of the microfinance market in Russia - S. N. Saifieva; I. V. Soklakova; A. V. Borshcheva; M. D. Ivanov (Вестник университета, 2024)
The relevance of the article is due to the insignificant contribution of microfinance to the development of the Russian economic system, especially in the context of supporting small and medium-sized businesses. However, the regulator sees it as a promising sector of the financial market and considers its progressive development necessary. The purpose of the work is to study the current state and identify trends in the development of the microfinance market in Russia. The methodological basis of the study includes empirical observation and analysis. During the work, official statistical data and scientific publications on the topic of microfinance have been used. The article provides a review of current legislative documents regulating the microfinance sector, and analyses the state of the market based on statistical data. It is substantiated that some elements of the monetary and financial policies pursued in the Russian Federation can be applied for the successful development of the microfinance sector, contribute to its effective and balanced work, and improve accessibility and sustainability. In the course of the work, key directions for the development of the microfinance market are formed: improving regulation and supervision; promoting financial literacy of the population; application of digital technologies; expansion and diversification of the product portfolio, development of partnerships, social entrepreneurship, which contribute to the sustainable development of this segment of the financial market. Particular attention is paid to a detailed analysis of improving the regulatory framework for microfinance in Russia from the point of view of legislation on bankruptcy of individuals, stimulating innovation and digitalisation, and supporting social entrepreneurship.